Correction procedures for extra-column effects in dynamic column breakthrough experiments - Rajendran, Arvind (2009)
Dynamic column breakthrough experiments, routinely used to complement adsorption and diffusion studies at the particle scale, constitute an important step in the development and verification of dynamic models for simulation of adsorption processes. Various parts of the experimental set-up contribute to the retention time